2019
DOI: 10.1021/acsmedchemlett.9b00394
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazole as a Replacement of the Electrophilic Group in Characteristic Prolyl Oligopeptidase Inhibitors

Abstract: 4-Phenylbutanoyl-aminoacyl-2(S)-tetrazolylpyrrolidines were studied as prolyl oligopeptidase inhibitors. The compounds were more potent than expected from the assumption that the tetrazole would also here be a bioisostere of the carboxylic acid group and the corresponding carboxylic acids are at their best only weak inhibitors. The aminoacyl groups L-prolyl and L-alanyl gave potent inhibitors with IC 50 values of 12 and 129 nM, respectively. This was in line with typical prolyl oligopeptidase inhibitors; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…In our previous studies, we have shown that a serine protease, prolyl oligopeptidase (PREP), increases aSyn oligomerization via direct protein‐protein interaction 15 , 16 and negatively regulates autophagy. 17 Importantly, small‐molecular PREP inhibitors can interfere with this interaction, leading to decreased aSyn aggregation, 15 , 18 , 19 and PREP inhibition or deletion also stimulates autophagy and increases the degradation of aSyn oligomers 16 , 17 , 18 and fibrils. 20 In aSyn‐based in vivo PD model, PREP inhibition has shown disease‐modifying impact by restoring an aSyn virus vector‐induced behavioural deficit.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have shown that a serine protease, prolyl oligopeptidase (PREP), increases aSyn oligomerization via direct protein‐protein interaction 15 , 16 and negatively regulates autophagy. 17 Importantly, small‐molecular PREP inhibitors can interfere with this interaction, leading to decreased aSyn aggregation, 15 , 18 , 19 and PREP inhibition or deletion also stimulates autophagy and increases the degradation of aSyn oligomers 16 , 17 , 18 and fibrils. 20 In aSyn‐based in vivo PD model, PREP inhibition has shown disease‐modifying impact by restoring an aSyn virus vector‐induced behavioural deficit.…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated that the effects of PREP ligands on αSyn dimerization and autophagy have no direct correlation to their IC 50 values. 15 , 16 Inhibition of the proteolytic activity has been thoroughly studied, but we are still learning how protein–protein interactions of PREP are regulated. PREP is a highly dynamic protein, where inhibitor binding restricts its conformational freedom, 17 and our working hypothesis is that the functions of PREP are dependent on what conformations PREP can adopt.…”
mentioning
confidence: 99%
“…In our previous study, we showed that a tetrazole ring could be directly attached to the inhibitor structure at the position of the electrophilic group without the important carbonyl group, resulting in moderately potent inhibitors 1a – e , and that the tetrazole ring was not a bioisostere of a carboxylic acid group. 16 In addition, the tetrazoles demonstrated clearly disconnected structure–activity relationships (SARs) for inhibition of the proteolytic activity and modulation of αSyn dimerization. In the present study, other nitrogen-containing five-membered heteroaromatics with different hydrogen-bonding capabilities and charges at physiological pH were investigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations